Manure placement influenced growth and dry matter yield of a plantain hybrid - Baiyeri, K.P.; Tenkouano, A. (African Crop Science Society, 2007)
The correct placement of fertilizer materials has a major effect on quantity of nutrient available for plant use and quantity lost through erosion and leaching. Thus, the effects of manure placement on whole-plant dry matter production and growth analysis traits were studied in a screen-house. Three manure placement methods, whereby they full dose of manure was applied as top-dressing (Trt 2), or a split combination thereof (Trt 3), were assessed together with a no manure control (Trt 4). Total dry weight, dry weights of root, leaf and non-leaf components were all significantly (P < 0.05) influenced by method of manure placement. Trt 1 supported the highest whole-plant dry weight at 12 WAP; however, this trend was not sustained as Trt 3 plants produced the highest total dry weight at 20 WAP. As expected, Trt 4 supported the least total dry weight at both sampling times. A larger proportion of dry matter produced at 12 WAP went into above surface components whereas dry matter distribution was less skewed at 20 WAP. Trt 3 supported partitioning of the highest (80.6%) photo-asimilate to above surface at 12 WAP at 12 WAP, but a 20 WAP, Trt 2 plants had the highest (62.7%) proportion of dry matter in above surface component. Physiological growth traits varied with manure placement such that RGR, ULR and SLA values were highest in Trt 3 while Trt 2 supported plants that had the highest values for LAR and LWF. The quantity of N in root and leaf had a positive and significant relationship with all the physiological growth traits. However, leaf K had the highest coefficient of correlation with whole-plant dry weight.